BRASSINOSTEROID‐SIGNALING KINASE 1 phosphorylating CALCIUM/CALMODULIN‐DEPENDENT PROTEIN KINASE functions in drought tolerance in maize. Issue 2 (17th May 2021) - Liu, Lei; Xiang, Yang; Yan, Jingwei; Di, Pengcheng; Li, Jing; Sun, Xiujuan; Han, Gaoqiang; Ni, Lan; Jiang, Mingyi; Yuan, Jianhua; Zhang, Aying
Summary: Drought stress seriously limits crop productivity. Although studies have been carried out, it is still largely unknown how plants respond to drought stress. Here we find that drought treatment can enhance the phosphorylation activity of brassinosteroid‐signaling kinase 1 (ZmBSK1) in maize ( Zea mays ). Our genetic studies reveal that ZmBSK1 positively affects drought tolerance in maize plants. ZmBSK1 localizes in plasma membrane, interacts with calcium/calmodulin (Ca 2+ /CaM)‐dependent protein kinase (ZmCCaMK), and phosphorylates ZmCCaMK. Ser‐67 is a crucial phosphorylation site of ZmCCaMK by ZmBSK1. Drought stress enhances not only the interaction between ZmBSK1 and ZmCCaMK but also the phosphorylation of Ser‐67 in ZmCCaMK by ZmBSK1. Furthermore, Ser‐67 phosphorylation in ZmCCaMK regulates its Ca 2+ /CaM binding, autophosphorylation and transphosphorylation activity, and positively affects its function in drought tolerance in maize. Our results reveal an important role for ZmBSK1 in drought tolerance and suggest a direct regulatory mode of ZmBSK1 phosphorylating ZmCCaMK.